2019
DOI: 10.1373/jalm.2018.027573
|View full text |Cite
|
Sign up to set email alerts
|

It's Not Just a Needlestick: Exploring Phlebotomists' Knowledge, Training, and Use of Comfort Measures in Pediatric Care to Improve the Patient Experience

Abstract: Background Blood draws are a routine element of the pediatric patient experience. They are also associated with the greatest fear and pain for a child. Because of the limited literature regarding phlebotomists' knowledge, experience, training, or stress related to their use of comfort techniques during pediatric blood draws, this study explored current practices and training methods. Phlebotomist training tends to focus on clinical technique rather than pediatric or patient comfort support. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Appropriate pain management is considered the most critical factor for parental satisfaction ( 30 ). Furthermore, venipuncture in children is a fairly challenging and stressful task for phlebotomists ( 31 , 32 ). When performing needle-related procedures with anxious children (or parents), they report experiencing a high level of stress ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate pain management is considered the most critical factor for parental satisfaction ( 30 ). Furthermore, venipuncture in children is a fairly challenging and stressful task for phlebotomists ( 31 , 32 ). When performing needle-related procedures with anxious children (or parents), they report experiencing a high level of stress ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also highlighted challenges in coping with parents, children with special needs and the nurses' own self-con dence during the procedure. An American study investigating phlebotomist experiences (33) described anxious patients and parents as a primary problem in relation to several aspects of blood sampling in children. Parents can often unwittingly transfer their own fears and anxiety to their children, something nurses must often be well-prepared to manage.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially helpful to work with phlebotomists who have experience with pediatric populations both for the comfort of the child and for the ease of the blood draw. A recent study found that almost half of phlebotomists surveyed lacked training in child development (Piazza et al, 2018), which can make it difficult to obtain a sample successfully. That same study found that the primary challenge to pediatric blood draws was anxiety in children and their parents (Piazza et al, 2018).…”
Section: Selected Serum Measures Of Cardiometabolic Healthmentioning
confidence: 99%
“…A recent study found that almost half of phlebotomists surveyed lacked training in child development (Piazza et al, 2018), which can make it difficult to obtain a sample successfully. That same study found that the primary challenge to pediatric blood draws was anxiety in children and their parents (Piazza et al, 2018). When conducting blood draws, it is best to schedule them in the morning as they often require fasting (e.g., 8 hr, water only).…”
Section: Selected Serum Measures Of Cardiometabolic Healthmentioning
confidence: 99%